The silent footsteps of danger: A qualitative study of methamphetamine use disorder - Gür, Çağla (Environment and Social Psychology, 2025)
Methamphetamine use disorder represents a growing global health concern, particularly affecting adolescents and young adults. Beyond its well-established neurotoxic effects, the substance imposes severe psychosocial consequences on individuals, families, and broader communities. This study aimed to provide a multidimensional understanding of methamphetamine dependence by combining psychiatric expertise with the lived experiences of an affected family. A qualitative design was employed, drawing on semi-structured interviews with 21 psychiatrists working in adult psychiatry departments and with members of a family directly impacted by methamphetamine addiction. Thematic analysis identified four overarching domains: (1) perceived trends in use, (2) psychiatric manifestations and diagnostic challenges, (3) social and environmental determinants, and (4) approaches to treatment and prevention. Findings demonstrated a marked increase in methamphetamine use among adolescents and young adults, with both clinicians and family members emphasizing the rapid transition from experimentation to dependence. Prominent psychiatric outcomes observed in methamphetamine dependence included intense paranoia, vivid hallucinations, episodes of aggression, and long-lasting cognitive deficits. These symptoms frequently made it challenging for clinicians to distinguish substance-induced states from primary psychotic illnesses. Beyond clinical manifestations, contextual influences played a critical role. Economic hardship, strained family relationships, parental mental health problems, and broader global uncertainties were repeatedly described as factors that heightened vulnerability. Excessive engagement with digital platforms and the anxiety provoked by constant exposure to social media further intensified these risks, while stigma and cultural silence often postponed both recognition of the problem and access to care. Importantly, the findings suggest that successful responses cannot rely on medication alone. The establishment of trusting therapeutic relationships, the introduction of preventive education during adolescence, the development of coping and problem-solving skills, and coordinated work across medical, psychological, and social domains emerged as vital elements of effective care. Taken together, these insights point to the need to approach Methamphetamine use disorder not only as a neuropsychiatric condition but also as a broader social phenomenon, one that demands integrated strategies spanning clinical practice, family systems, and community support structures.